Educational Approach to Prevent the Burden of Vaccinia Virus Infections in a Bovine Vaccinia Endemic Area in Brazil - Galileu Barbosa Costa; Jaqueline Silva de Oliveira; Michael B. Townsend; William C. Carson; Iara Apolinário Borges; Andrea M. McCollum; Erna Geessien Kroon; Panayampalli Subbian Satheshkumar; Mary G. Reynolds; Yoshinori J. Nakazawa; Giliane de Souza Trindade (Pathogens, 2021)
Bovine vaccinia (BV), caused by Vaccinia virus (VACV), is a zoonotic disease characterized by exanthematous lesions on the teats of dairy cows and the hands of milkers, and is an important public health issue in Brazil and South America. BV also results in economic losses to the dairy industry, being a burden to the regions involved in milk production. In the past 20 years, much effort has been made to increase the knowledge regarding BV epidemiology, etiologic agents, and interactions with the hosts and the environment. In the present study, we evaluated milking practices that could be associated with VACV infections in an endemic area in Brazil and proposed an educational tool to help prevent VACV infections. In our survey, 124 individuals (51.7%) from a total of 240 had previously heard of BV, 94 of which knew about it through BV outbreaks. Although most individuals involved in dairy activities (n = 85/91) reported having good hygiene practices, only 29.7% used adequate disinfecting products to clean their hands and 39.5% disinfected cows’ teats before and after milking. Furthermore, 46.7% of individuals reported having contact with other farm and domestic animals besides dairy cattle. We also evaluated the presence of IgG and IgM antibodies in the surveyed population. Overall, 6.1% of likely unvaccinated individuals were positive for anti-Orthopoxvirus IgG antibodies, and 1.7% of all individuals were positive for IgM antibodies. Based on our findings, we proposed educational materials which target individuals with permanent residence in rural areas (mainly farmers and milkers), providing an overview and basic information about preventive measures against VACV infections that could enhance BV control and prevention efforts, especially for vulnerable populations located in endemic areas.